2004
DOI: 10.1111/j.1432-1033.2004.04230.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial malate dehydrogenase from the thermophilic, filamentous fungusTalaromyces emersonii

Abstract: Mitochondrial malate dehydrogenase (m-MDH; EC 1.1.1.37), from mycelial extracts of the thermophilic, aerobic fungus Talaromyces emersonii, was purified to homogeneity by sequential hydrophobic interaction and biospecific affinity chromatography steps. Native m-MDH was a dimer with an apparent monomer mass of 35 kDa and was most active at pH 7.5 and 52°C in the oxaloacetate reductase direction. Substrate specificity and kinetic studies demonstrated the strict specificity of this enzyme, and its closer similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…fungi, such as H. lanuginosa (5.8 mM) and M. pusillus (4.44 mM), T. emersonii (1.0 mM), and P. infestans (0.64 mM). 20,25,26,30) With NADH as co-substrate, the K m value for ScMDH (0.083 mM) was very similar to the data for S. aureofaciens MDH (0.085 mM) and P. infestans mMDH (0.086 mM). 20,30) Recombinant ScMDH displayed a similar K m value for NAD þ (0.15 mM), corresponding to enzymes from S. aureofaciens (0.27 mM) and fungi T. emersonii (0.13 mM), C. neoformans (0.11 mM), H. lanuginosa (0.1 mM), and M. pusillus (0.16 mM).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…fungi, such as H. lanuginosa (5.8 mM) and M. pusillus (4.44 mM), T. emersonii (1.0 mM), and P. infestans (0.64 mM). 20,25,26,30) With NADH as co-substrate, the K m value for ScMDH (0.083 mM) was very similar to the data for S. aureofaciens MDH (0.085 mM) and P. infestans mMDH (0.086 mM). 20,30) Recombinant ScMDH displayed a similar K m value for NAD þ (0.15 mM), corresponding to enzymes from S. aureofaciens (0.27 mM) and fungi T. emersonii (0.13 mM), C. neoformans (0.11 mM), H. lanuginosa (0.1 mM), and M. pusillus (0.16 mM).…”
Section: Discussionsupporting
confidence: 62%
“…2B), similarly to the MDHs from three thermophilic fungi, H. lanuginosa (50 C), M. pusillus (50 C), and T. emersonii (52 C). 25,26) Thermal inactivation studies have indicated that ScMDH is thermostable, with an estimated t 1=2 of 120 min at 50 C (Fig. 3B), much more thermostable than MDHs from thermophilic fungi reported so far, 27) in spite of the fact that it is less thermostable than MDHs from a few extremely thermophile bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations